Isolation, Identification, and Evaluation of Antimicrobial Activity of Active Compound Produced by Marine Actinomycetes isolate A32 - Sunaryanto, Rofiq; Marwanta, Edy (ANNALES BOGORIENSES, 2015)
Isolation, identification, and evaluation of antimicrobial activity of active compound produced by marine actinomycetes isolate A32 has been conducted. Production of active compound using isolate A32 was conducted by glucose, yeast, peptone medium. The fermentation was carried out at 30ÂºC for 5 days. The broth of supernatant was extracted using ethyl acetate. Purification of active compound used column chromatography and eluted stepwise with the chloroform and methanol solvent. Antimicrobial activity was monitored by the agar diffusion, and microbial test used as followed Escherichia coli ATCC 25922, Staphylococcus aureus ATCC25923, Bacillus subtilis ATCC 66923, and Candida albican BIOMCC00122. Results of isolation and purification of active compound produced by isolate A32 showed that this compound has a molecular weight of 503.1 g/mol with molecular formula C26H37N3O7. Analysis of spectrum using 1HNMR and COSY, this compound was suspected as Madumycin II. The antibacterial activity assay showed that this active compound was able to inhibit to the growth of Staphylococcus aureus ATCC25923 and Candida albican BIOMCC00122.